2021
DOI: 10.1039/d1nj02488d
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption isotherms and kinetic studies for the removal of toxic reactive dyestuffs from contaminated water using a viologen-based covalent polymer

Abstract: A polyviologen-based adsorbent was prepared via polymerization of a viologen-dialdehyde with a hydroxyl-substituted aryl-dihydrazide in acidified water. The viologen-based covalent polymer aerogel was then generated by freeze-drying. The adsorption of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Several studies have reported maximum adsorption for anionic dyes at acidic pH. 15,[47][48][49][50] Under neutral and alkaline conditions, the functional groups of C1@CsNPs become either neutral or deprotonated. Thus, electrostatic attractions disappear, consequently, the R% of DR31 decreases.…”
Section: Effect Of Adsorption Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported maximum adsorption for anionic dyes at acidic pH. 15,[47][48][49][50] Under neutral and alkaline conditions, the functional groups of C1@CsNPs become either neutral or deprotonated. Thus, electrostatic attractions disappear, consequently, the R% of DR31 decreases.…”
Section: Effect Of Adsorption Parametersmentioning
confidence: 99%
“…Also, several reports found that the PFO gives the best t to the experimental data. 15,[57][58][59][60][61] For Pb 2+ adsorption, Table 2 shows that Elovich model has the highest R 2 and lowest error values indicating that the adsorption kinetics can be accurately described by Elovich model. Thus, according to Elovich assumptions, the adsorption of Pb 2+ onto C1@CsNPs follows a chemisorption process involving surface chelation, electron-transfer, and/or sharing/ exchange of electrons between C1@CsNPs and Pb 2+ .…”
Section: Effect Of Adsorption Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several treatment methods such as flocculation, ultrafiltration, and the biological method have been used in textile wastewater treatment and have been shown to be inefficient. On the contrary, the adsorption process, which is widely used, has been shown to be highly effective and more economical. , Numerous materials have been used as adsorbents. Among them, magnetic zero-valent-based bimetallic nanoparticles (NPs) have attracted growing interest owing to their promising features.…”
Section: Introductionmentioning
confidence: 99%
“…These wastewaters contain a variety of organic and inorganic contaminants (Liu et al 2021 ). Synthetic organic dyes are one of the largest groups of organic contaminants because of their extensive use in several industries (Kasumov et al 2021 ; Nour et al 2021 ). The features of synthetic dyes such as bio-recalcitrance, toxicity, carcinogenicity, mutagenicity, and light absorbance make them harmful to humans and aquatic environment (Kasumov et al 2021 ; Nour et al 2021 ; Zhang et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%